Molecular epidemiology of Ascaris lumbricoides following multiple rounds of community-wide treatment - Toby Landeryou; Rosie Maddren; Jack Hearn; Mahlet Belachew; Santiago Rayment Gomez; Ewnetu Firdawek Liyew; Kathryn Forbes; Birhan Mengistu; Scott P. Lawton; Jude Eze; Geremew Tasew; Ufaysa Angulo; et al. (Nature Communications)
Abstract Control and elimination of the parasite Ascaris lumbricoides relies on mass drug administration (MDA) using a limited number of anti-helminthics. Whilst these programs have reduced the infection intensity and prevalence within many endemic regions, patterns of transmission remain poorly understood. Reinfection commonly occurs following cessation of treatment due to the absence of acquired immunity post infection. Here, we utilise genomic data to understand parasite transmission within and between households in a community and the genomic impact of repeated MDA. We sequenced 54 whole-genomes from Ascaris worms obtained from individuals in a longitudinal cohort epidemiological study of transmission and drug treatment extending over 6 years. We found that fine-scale population structure exists in spatially distinct clusters of infected individuals with reinfection occurring within or between geographically close households. This observation helps inform the policy for future control in low prevalence settings suggesting more targeted treatment of infection hotspots. We found evidence of positive selection acting on members of gene families previously implicated in reduced drug efficacy but detected no impactful variants. As efforts to eliminate A. lumbricoides intensify, our study provides a foundation for genomic surveillance to help identify both who infects whom and the impact of repeated drug treatment.